Watch me disappear [compact disc, unabridged] : a novel - Brown, Janelle (Penguin Random House, 2017)
When a Berkeley mother with a radical past goes missing during a hike in California's Desolation Wilderness, her devastated family is forced to come to terms with her secretive nature.